1992
DOI: 10.1007/bf00176177
|View full text |Cite
|
Sign up to set email alerts
|

Song overproduction and selective attrition lead to song sharing in the field sparrow (Spizella pusilla)

Abstract: Male field sparrows settling on particular territories for the first time often sing two or more song types. Vocal experience with neighboring males then leads in most cases to the deletion from the male's repertoires of all but one song type. In 2 years, settling males retained the song type that most closely resembled that of a neighbor. Focal observations in 1 year revealed that the most actively singing neighbor was the one the new birds resembled. Songs were not selected on the basis of their absolute aco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
52
0

Year Published

1996
1996
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(54 citation statements)
references
References 41 publications
2
52
0
Order By: Relevance
“…Thus, sexual selection or the need for social song adjustment rather than brain autonomous maturation processes might play a role for the decrease in repertoire size and song duration in female cordon-bleus and for the change of repertoire composition in both males and females, independent of gross morphological changes. On more ultimate terms, developmental overproduction of song patterns followed by repertoire attrition has been described for several species and has been interpreted in the context of social adjustments of repertoires (e.g., Marler and Peters, 1982;Nelson, 1992;Geberzahn et al, 2002). Future long-term monitoring of cordonbleus shall show if females and males of this species classify as open-ended vocal learners in contrast to other Estrildid finches such as the zebra finch.…”
Section: Developmental Mechanisms Of Hvc and Ra Sizementioning
confidence: 99%
“…Thus, sexual selection or the need for social song adjustment rather than brain autonomous maturation processes might play a role for the decrease in repertoire size and song duration in female cordon-bleus and for the change of repertoire composition in both males and females, independent of gross morphological changes. On more ultimate terms, developmental overproduction of song patterns followed by repertoire attrition has been described for several species and has been interpreted in the context of social adjustments of repertoires (e.g., Marler and Peters, 1982;Nelson, 1992;Geberzahn et al, 2002). Future long-term monitoring of cordonbleus shall show if females and males of this species classify as open-ended vocal learners in contrast to other Estrildid finches such as the zebra finch.…”
Section: Developmental Mechanisms Of Hvc and Ra Sizementioning
confidence: 99%
“…In many seasonal, migratory songbirds, however, vocal learning often has to be mastered in a shorter period. For example, the song of a yearling migratory male often closely matches that of an adult close neighbor first encountered when the yearling migrant arrives at the spring breeding grounds (6)(7)(8)(9)(10). How such fast and precise song matching is achieved remains controversial (11)(12)(13).…”
mentioning
confidence: 99%
“…How such fast and precise song matching is achieved remains controversial (11)(12)(13). One way to do it would be for a juvenile to imitate a diversity of external models during its hatching year and then during the following spring retain only the imitation that best matches the song of a neighbor with whom it interacts (8,11,14,15). However, songs acquired during the hatching year might not come close to the song of breeding-season neighbors.…”
mentioning
confidence: 99%
“…For instance, if the overlap in syllable composition reflects genetic relatedness, females can avoid mating with individuals that are closely related to them (Stoddard, 1996). As for culturally selected songs, females may prefer individuals that use the local dialect composed of specific syllables, because these males may have high local experience on the breeding grounds (Nelson, 1992). For example, it has been suggested that the females of the great reed warbler Acrocephalus arundinaceus discriminate between philopatric and immigrant males based on the presence of specific whistles, which may provide the females with a clue about males' origin .…”
Section: Discussionmentioning
confidence: 99%